Necesidad de reformar el numeral 2 del Artículo 46 de la constitución de la república, para prohibir el trabajo de menores de 18 años de edad, debido a los riesgos a los cuales se encuentran expuestos - Ortiz Calva, Sergio Francisco (2017)
Since the appearance of man on the face of the earth begins to work through the physical effort to get their food and start adapting spaces for the night, then building basic housing to secure their place in a particular sector, with the passing time work was regulated by the struggle of the workers until their activity is not precarious. Child labor in its infancy allowed employers enrichment, both labor exploitation, being cheap labor, the occupation of this population group gender misery in their families by job insecurity in which it developed. the work of adolescents aged 15 to 17, has the same story, but in most countries in South and Central America work is permitted exceptions in health, personal development and education, but any work activity generates risks, same labor law at the international and local level regulated as risks, occupational diseases and accidents, it is easy to see that by working on the street there are risks of accidents, be induced to gangs and enter a flagellum is deadly as drug addiction, dependency relationship work generates physical, psychological abuse by the employer, what about the domestic work of adolescent women risks in physical, psychological and sexual integrity are a daily chores. The legislation to regulate child labor and adolescents as stipulated in Article 46, paragraph 2, of the State Constitution, and Articles 82, 84 and 89 of the Code of Children and Adolescents, which in theory sounds perfect , is nonetheless in very good intentions, but in practice is not met, by these considerations believe relevant this amendment to the Constitution to prohibit the employment of children under 18 years for the risks to which they are exposed, no longer for some a utopia, but we believe that our proposal we have theoretically justified, practical and legal.